Antibacterial and hemolytic activity of cationic polymer-vancomycin conjugates - AKSU, MEHMET BURAK (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
In this study, a Gram positive bacteria effective anti-biotic, vancomycin (VAN), was conjugated with antimicrobial cationic polymers (ACPs) that were found to be active against both Gram positive and Gram negative bacteria previously, and the antibacterial activity of newly synthesized VAN-PEG-ACP conjugates were investigated. VAN was first PEGylated using Michael Addition method, then the ACPs, which were synthesized using ring-opening metathesis polymerization (ROMP), were bound covalently to the VAN-PEG structure using cross metathesis pathways and thus cationic polymer-vancomycin conjugates (VAN-PEG-ACPs) were obtained. The antimicrobial activity of the conjugates were investigated against Gram negative strain E. coli and Gram positive strains S. aureus and E. feacalis. Con_1_10k_1, Con_2a_3k_1, and Con_2b_3k_1 were found to be active towards S. aureus (MIC = 64 mu g/ml, 32 mu g/mL, and 32 mu g/mL, respectively) and Con_2a_3k_1, and Con_2b_3k_l were found to be active also towards E. feacalis (MIC = 16 mu g/ml and 32 mu g/mL, respectively), however they did not show activity towards E. coli. All the conjugates were found to be non-hemolytic towards red blood cells (HC50 = > 1024 mu g/mL). MTS assay results also showed that the conjugates did not lyse viable HUVEC cells within 72 h. The membrane deformation of S. aureus was monitored using scanning electron microscopy (SEM) techniques in the presence of the polymers and the conjugates.
Keywords: Vancomycin; Cross metathesis; Antimicrobial activity; Hemolytic concentration; Cytotoxicity; DE-NOVO DESIGN; ANTIMICROBIAL POLYMERS; NITRIC-OXIDE; DEFENSE; PEPTIDES; DELIVERY; MIMICS; ACID